Functional impairment in adults positively screened for attention-deficit hyperactivity disorder: The role of symptom presentation and executive functioning - Szuromi, Bálint; Bitter, István; Czobor, Pál (Comprehensive psychiatry, 2013)
While the number of symptoms of attention-deficit hyperactivity disorder (ADHD) decreases with age, a high proportion of adults with ADHD symptoms suffer from persistent functional impairment (Fi) linked to these symptoms. Our objective was to investigate the specific roles of two potentially important predictors of this Fi: the clinical symptom presentation and the deficit in executive functions (EFs). A total of 158 subjects from a community sample positively screened for ADHD were classified into two groups: those with and without Fi. Following a detailed diagnostic process, participants were administered a self-rating scale for ADHD symptoms as well as a neuropsychological test battery containing tests of EF and attention relevant as potential cognitive endophenotypes for ADHD. The overall number as well as the number of inattentive, hyperactive and impulsive symptoms, confirmed both by examiner and self-report, were significantly higher among Fi subjects. The highest odds ratio for Fi was associated with impulsive symptoms. Additionally, self-reported complaints of problems with self-concept were significantly higher among Fi subjects. No significant relationship between Fi and neuropsychological measures of EF and attention was detected. This study revealed that the number of symptoms, in particular that of impulsivity, had a significant impact on Fi in adults with symptoms of ADHD. Furthermore, our results underline the importance of assessing complaints and behaviors related to self-concept, which are not included in DSM-IV diagnostic criteria of ADHD but nonetheless may be associated with functional outcome of the disorder.